Energy and exergy efficiencies enhancement analysis of integrated photovoltaic-based energy systems. (December 2019) - Ogbonnaya, C.; Turan, A.; Abeykoon, C.
Highlights: This study proposes novel energy and exergy efficiencies enhancement analysis approach for analysing systems with parent-offspring relationship. The proposed approach is applied with actual temperature and solar radiation data from Nigeria to study four photovoltaic-led energy systems. The design and cost implications of conversion and usage losses recovery are highlighted. Abstract: Integrated energy systems (IESs) take advantage of the complementarity of their subsystems to improve the overall system functionality, sustainability and performance. Presently, the cost of the recovery of thermodynamic losses from photovoltaic modules has not been addressed. In this study, novel energy and exergy efficiencies enhancement analysis (EEEEA) is proposed for the study of the implications of recovering the conversion and usage losses from a photovoltaic (PV) module. Four evolutionary IES were analysed: a PV-Battery (System 1); a Photovoltaic-thermal (PV/T)-Battery (System 2); a PV-Battery-Electrolyser-Fuel cell (System 3) and a PV/T-Battery-Electrolyser-Fuel cell (System 4). Actual solar radiation and temperature data coupled with synthesised data were applied. Results show that both the energy and exergy efficiencies of System 2 upgraded by 27.89% and 5.42%, respectively, over System 1. The energy and exergy efficiencies of System 3 degraded by 3.11% and 4.10%, respectively, over System 1; whereas the energy and exergy efficiencies of System 4 degraded by 21.92% and 7.72%, respectively, over System 2. Furthermore, the thermodynamic efficiencies of the IESs did not naturally upgrade with system complexity. The EEEEA can help scientists, engineers and policymakers to analyse IESs with a parent-offspring relationship in order to establish the optimum efficiency and thermo-economics.